Rare Case of a Young Male Presented with Abdominal Pain, Solid Colon Tumors, and Eosinophilia, Followed by Tremendous Thromboembolic Complications and Eventually Diagnosed with Idiopathic Hypereosinophilic Syndrome - Tomasz Zemleduch; Anna Czapla; Piotr Kimla; Bartosz Kudliński (Case Reports in Medicine)
Hypereosinophilic syndrome (HES) is a rare condition characterized by profound peripheral eosinophilia and various organ dysfunction. Diagnostic criteria and classification of this challenging medical entity changed over time. Elevated absolute eosinophil count with extensive tissue infiltration and signs of organ damage of unknown origin is termed idiopathic HES. Hypereosinophilia is a highly hypercoagulable state; thus, a variety of thromboembolic complications may occur. Only a few reports of idiopathic HES patients with different forms of thrombosis are being published. We document a case of a young male presented with persistent abdominal pain with two eosinophilic colon tumors. The patient suffered from phlegmasia cerulea dolens and portal vein thrombosis, followed by pulmonary embolism and overt disseminated intravascular coagulation (DIC). Corticosteroids successfully reduced and controlled eosinophil level while skilled anticoagulation and supportive management overcome DIC-associated complications.